2016
DOI: 10.1589/jpts.28.1448
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tight clothes on cervical and thoracic spine muscles during shoulder abduction

Abstract: [Purpose] The purpose of this study was investigated the effect of tight clothes on cervical and thoracic spine muscles activities during shoulder abduction. [Subjects and Methods] The subjects of this study were 10 healthy males. The subjects performed two shoulder abduction trials for each of two jacket-wearing conditions. The right upper, middle, and lower trapezius and serratus anterior muscles activities were measured using a surface electromyography system during right shoulder abduction. [Results] The u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 3 publications
0
1
0
Order By: Relevance
“…In current study 18.8% (n=35) had Clothing can directly affect the physiology (Na, 2015). Another study showed that if waring tight-jacket conditions compared with the general-jacket conditions the muscle of serratus anterior and lower trapezius and muscle activity limited and lead to decrease normal scapular movements lead to pain and discomfort in tight jacket condition (Kim and Yoo, 2016).…”
Section: Resultsmentioning
confidence: 54%
“…In current study 18.8% (n=35) had Clothing can directly affect the physiology (Na, 2015). Another study showed that if waring tight-jacket conditions compared with the general-jacket conditions the muscle of serratus anterior and lower trapezius and muscle activity limited and lead to decrease normal scapular movements lead to pain and discomfort in tight jacket condition (Kim and Yoo, 2016).…”
Section: Resultsmentioning
confidence: 54%